Sensibilidade da mama antes e após a mamoplastia com cicatriz curta em L - Armando Chiari Junior (2006)
Breast sensitivity preservation is one of the aims to be achieved bymodern breast surgery but the literature on the subject is scarce and contradictory. The purpose of this work was to prospectively study the breast sensitivity of 64 patients who underwent surgery with the L short scar mammaplasty technique. The breasts (n = 125) were tested one day before surgery, as well as six months and twelve months after it, with Semmes-Weinstein monofilaments. Nine points on each breast were tested: the nipple, four cardinal points on the areola and four cardinal points on the skin. Breasts were classified in three groups, according to the mammary tissue weight resected: group A up to 200 g, group B from 201 to 400 g and group C over 400 g. The ruskal-Wallis Test was used in order to compare breast region sensitivity in the different groups, in distinct periods. The Friedman Test was used to compare the evolution of sensitivity of the same breast in different operative periods in each group separately; p<0.05 values were considered to be statistically significant. The L short scar mammaplasty technique and surgical maneuvers carried out to preserve the anterior divisions of the lateral cutaneous branches of the intercostal nerves were described. Before surgery it was noticed that breast skin sensitivity was significantly less intense with the increase on breast ptosis (grades I, II and III; p=0.021). It was also noticed a relation between larger breasts volumes and less sensitivity in areola regions (groups B and C; p<0.001) and on skin (group C; p<0.001). Twelve months after surgery it wasnt observed a relation between larger resected volumes and less breast sensitivity. In nipple-areola complexes, all groups reached sensitivity levels without significant difference in relation to pre-operative levels, from six to twelvemonths after surgery. After six and twelve months, significantly more intense sensitivity levels on breast skin were verified in resections of more than 200 g (group B; p=0.002 and group C; p<0.001). Patients were also subjectively evaluated, answering a questionnaire 12 months after surgery. From the total, 89.1% reported that nipple-areola complex sensitivity didnt disappear even on the first days of the post-operative period. After 12 months, no patient reported areola or nipple insensitivity areas; 66.4% from the total of patients and 94.4% from group C patients (mammary tissue resection mean of 499 g) reported areola or nipplesensitivity equal to or better than pre-operative sensitivity. In conclusion, after the L short scar mammaplasty, breast sensitivity to pressure returns to pre-operative levels or improves and most patients get pleased with areola or nipple sensitivity intensity and quality, mainly those with larger breasts